Dynamics and correlation of microbial community and flavor in Pixian Douban fermented with closed process of constant temperature. (19th January 2021) - Ding, Wenwu; Zhao, Xiaoyan; Xie, Si; Liu, Yan; Zhang, Manna; Che, Zhenming; Liu, Yi; Liu, Ping; Lin, Hongbin
Abstract: BACKGROUND: As a Chinese traditional flavor condiment, Pixian Douban (PXDB) is produced using a traditional open fermentation process. In this study, an experimental fermentation of PXDB was conducted at 40 °C for 90 days in a closed system, which has not been applied to PXDB production. The flavor, microbial community and correlations of the samples in the closed system were compared with those in the traditional fermentation. RESULTS: The content of organic acids and free amino acids in the closed fermentation of constant temperature (CFCT) achieved the standards of product quality, although they were lower than those in the traditional fermentation. Of the 140 detected aroma components, 98 were shared in the two fermentation processes. Enterobacter, Bacteroides and Megamonas were the core microbial genera related to 26 flavor components in the traditional fermentation, while Pantoea was the core microbial genus related to 18 flavor components in CFCT. The CFCT has its own unique advantages over traditional fermentation in forming aromas. It produced a greater impact on the succession of fungi than those of bacteria after changing traditional fermentation to CFCT. The influence of microorganisms on the formation of flavor components was relatively more balanced in CFCT, while the changed fermentation process impacted greatly on the functions of Zygosaccharomomyces and Pichia but little on those of Sphingomonas, Megamonas and Parabacteroides . CONCLUSION: The study indicated that it was feasible to ferment PXDB in the closed system, and provides a basis to realize controllable PXDB production. © 2020 Society of Chemical Industry